Relacje syna z ojcem na przykładzie osób ćwiczących w siłowniach = Relationship between father and son on the example of men exercising in gyms - Maciejewska, Tatiana (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article is to present a fragment of research on the perception and creation of male identity by men exercising in gyms. This passage refers to fatherhood and creating relationships in the body building context. The article describes the oscillation between a traditional and a new paradigm of masculinity. The feminist concept of men?s studies is interwoven with the traditional approach to masculinity. For many men, building a male-female relationship takes place through the negotiation of rights and obliga tions. Contemporary approach to masculinity has opened a way to take full advantage of fatherhood. Finding a paternal instinct and care for the child, with affection once reserved exclusively for the mother, both of them are currently considered the ultimate goals of fatherhood. The researcher was interested in knowing whether men duplicate paternity patterns imprinted in the process of socialization, or have developed their own models, based on individual relationship with the child.
Keywords: tacierzyństwo; men's studies; relacje w związkach; męskość; fatherhood; relationship; masculinity